Xylophagia: a meta-synthesis of the literature. Issue 4 (28th November 2019) - Choudhry, Fahad Riaz; Munawar, Khadeeja; Akram, Bushra; Al-Worafi, Yaser Mohammed; Bakrin, Faizah Safina; Tey, Li Ying; Jacob, Sabrina Anne; Hing, Goh Bey; Khan, Tahir Mehmood; Han, Lee Learn; Kamal, Anila
Abstract : Purpose: The purpose of this paper is to provide an insight into xylophagia, its treatment, intervention options, etiological causes and possible relationship with other diseases. Design/methodology/approach: A systematic search was performed across four scientific databases (i.e. Ovid Medline, Embase via Ovid, PubMed and ProQuest). All of the qualitative studies reporting on xylophagia from the inception of databases until August 2019 have been included. The quality of included studies was assessed through a ten-item checklist given by Kmet et al. (2004). Findings: A total of 18 studies were included, and five primary themes emerged after analysis: precipitation/onset of xylophagia, co-morbid psychiatric or medical illnesses, assessment and investigation modes to confirm diagnosis, outcomes of xylophagia and treatment options comprising medical care, psychological care, counseling and duration of recovery. There were 16 females and 9 males in included studies. The mean ages and standard deviations of males and females were 29.25(12.17) years and 32.81(11.92), respectively. The mean duration and standard deviation of paper pica were 4.80(4.27) years. Research limitations/implications: Despite the limitation that this meta-synthesis is based upon findings from case studies, results show that standardized medication regimens for treating xylophagia are still not available or are unknown. There is a dire need for further research in order to better understand the disorder. The healthcare professionals need to use reciprocal, mutually constituent influence of biological and sociocultural factors in order to screen, diagnose and manage complex psychological problems like xylophagia. Originality/value: The findings advance our understanding of the positive effects of patients and family members undergoing counseling or cognitive behavior therapy in reducing stress and enhancing coping skills thus, avoiding self-damaging behaviors.